PROFIL BIOAUTOGRAFI DAN UJI PENANGKAP RADIKAL 2,2-DIFENIL-1-PIKRIHIDRAZIL OLEH EKSTRAK ETANOL DAUN BINAHONG (Anredera scandens (L.) Moq.) DAN FRAKSI-FRAKSINYA - Samirana, P. O.; Swastini, D. A.; Putra, A. A. G. R. Y.; Kusuma, I P. W.; Pratiwi, N. P. A. Y.; Setiawan, V. A. (Jurnal Kimia (Journal of Chemistry); Vol.14 No.1 Januari 2020DO - 10.24843/JCHEM.2020.v14.i01.p03, 2020)
Free radicals are atoms or molecules that have one or more unpaired electrons and are highly reactive. Antioxidants can inhibit the excessive oxidation reaction. The leaves of binahong (Anredera scandens (L.) Moq.) are one part of plants which contain flavonoid compounds and tannins that have scientific activity as antioxidants.This study aims to determine the bioautographic profile and to test the antioxidant activity of the ethanol extract of the leaves of Anredera scandens (L.) Moq. useing 2.2-diphenyl-1-pikrilhidrazil radical capture method. The extraction process produced 19.22% yield, 14.68% (14.684 grams) chloroform fraction, 11.22% (11.224 grams) n-hexane fraction, 3.09% (3.094 grams) ethyl acetate fraction, and 23.90% (23.904 grams) n-butanol fraction. The results of bioautographic profile test using KLT densitometry method proved that ethanol extract, chloroform fraction and ethyl acetate fraction have DPPH radical capture activities. The determination of total flavonoid content found that ethyl acetate fraction contained higher total flavonoids than other fractions. In the ethyl acetate fraction, high total flavonoid level and low IC 50 values were obtained, while the n-hexane fraction had low flavonoid level and high IC 50 values.   Keywords: antioxidants, binahong leaves, free radicals, flavonoids, IC50.